Macroeconomics in context - Goodwin, Neva R (Routledge, 2019)
Macroeconomics in Context lays out the principles of macroeconomics in a manner that is thorough, up to date, and relevant to students. Like its counterpart, Microeconomics in Context, the book is uniquely attuned to economic realities. The "in Context" books offer engaging coverage of current topics including financial crises, rising inequality, debt and deficits, and environmental sustainability, while also providing a clear and accessible exploration of economic theory and applications.